Hubungan Kebisingan Dengan Stres Kerja Pada Operator di PT Kusumaputra Santosa - Bachtiar Chahyadhi; Rizky Ayu Mukharomah; Tutug Bolet Atmojo (Journal of Applied Agriculture, Health, and Technology, 2022)
An industrial development is always followed by technological developments, especially in the textile industry which in the process cannot be separated with the help of machines. One of the negative impacts of this development is the noise from activities that use machines. Noise can be interpreted by the brain as a stressor or a trigger for stress. This study aims to determine the relationship between noise and work stress on operators at PT Kusumaputra Santosa. This type of research is analytic observational with a cross sectional approach. The sample of this study were 43 workers in the spinning division at PT Kusumaputra Santosa. The sampling technique in this study used a purposive sampling technique. To measure noise using a Sound Level Meter (SLM). While the bivariate analysis technique used to determine the correlation between noise and work stress is the Somers'd test. The results of the study using the Somers'd test showed that there was a correlation between noise and work stress on the spinning operator with a p-value of 0.000 and correlation (r) = 0.516 (medium correlation strength). Suggestions for further research need to add other variables or factors that can affect work stress that have not been studied in this study, such as work relations, organizational structure, work atmosphere and work climate. For companies, it is necessary to upgrade personal protective equipment with better quality than before and comfortable to wear and for spinning workers, they need to wear earplugs that have been provided by the company.